Preparation method of PLA porous foam material
By mixing, extruding and foaming the lignocellulose extracted from agricultural waste with polylactic acid particles, bio-based porous foam materials are prepared, solving the problems of environmental unfriendliness and high cost of existing rigid foam materials. , achieves stability and insulation effects, and promotes a sustainable circular economy.
Patent Information
- Application Number
- CN202310973259.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-03
- Publication Date
- 2025-02-14
AI Technical Summary
Existing rigid foam materials such as EPS are unfriendly to the environment after production and use, and are costly, making it difficult to achieve a sustainable circular economy.
Bio-based porous foam material is prepared by crushing agricultural waste (such as corn stalks, wheat stalks, etc.) and extracting lignocellulose, combined with polylactic acid granules for kneading, extruding and foaming.
The stability and thermal insulation effect of bio-based porous foam materials are achieved, production costs are reduced, agricultural waste is effectively utilized, and sustainable circular economy is promoted.
Abstract
Description
Technical Field
[0001] The present application relates to a method for preparing a PLA porous foam material, and belongs to the technical field of bio-based composite materials. Background Art
[0002] Foams are an important part of everyday life for people around the world. They are used in a variety of applications, including packaging, insulation and disposable food containers. Expanded polystyrene (EPS), often referred to by the brand name Styrofoam, is the current rigid foam TM One of the industry standards.
[0003] While EPS is well suited for insulation and packaging applications and is low-cost, it is not a sustainable option. Similar to other petroleum-based foams, the production of EPS involves the consumption of non-renewable resources, which are typically discarded in landfills after a single use. While governments and companies around the world have made great progress in increasing recycling efforts, including for foam materials, more sustainable options are still needed to achieve a circular economy.
[0004] Bio-based polymers are a popular route taken by researchers to improve the environmental friendliness of rigid foams. Studies have shown that replacing petroleum-based polymers with bio-based polymers can reduce emissions that are harmful to the environment and human health. Many bio-based polymers are also biodegradable or industrially compostable, which can reduce accumulation in landfills. Some work has demonstrated that bio-based polymer foams can be made using industrially scalable methods and can achieve properties similar to traditional industry standards. In particular, polylactic acid (PLA) is a promising bio-based option due to its physical properties (often compared to polystyrene and polypropylene) and its compostability. But the main problem with PLA remains its cost and insufficient performance.
[0005] Agricultural straw is an important lignocellulose resource - rich, renewable and degradable. Low cost. my country is vigorously promoting the comprehensive utilization of straw and promoting the quality and efficiency of the straw comprehensive utilization industry. Adhere to agricultural use first, continue to promote the use of straw as fertilizer, feed and base material, and give full play to the functions of straw in farmland conservation and the combination of planting and breeding. Expanding the scale of straw clean energy utilization, encouraging the use of straw and other biomass energy for heating and gas supply, optimizing the rural energy structure, and promoting the application of biomass natural gas in the industrial field are the current main directions. Summary of the invention
[0006] The object of the present application is to provide a bio-based agricultural waste / PLA porous foam material, which has the advantages of stability and heat insulation.
[0007] According to one aspect of the present application, a method for preparing a PLA porous foam material is provided, comprising the following steps:
[0008] S1, crushing the biomass material, extracting lignin and cellulose nanofibers therein, and homogenizing them to obtain lignocellulose;
[0009] S2, mixing the polylactic acid particles and the wood cellulose to obtain a mixed masterbatch, and extruding and foaming to obtain the PLA porous foam material;
[0010] The biomass material is selected from corn straw, wheat straw, rice husk, rice straw, cotton straw, tobacco straw, sugarcane bagasse, and grape prunings.
[0011] crushing the biomass material to obtain crushed biomass material;
[0012] The particle size of the crushed biomass material is 500-600 meshes.
[0013] The extraction includes the following process:
[0014] (1) boiling and drying the crushed biomass material, soaking it in a sodium hydroxide aqueous solution and performing ball milling to obtain a solid and an alkali solution;
[0015] (2) washing the solid to neutrality, dispersing it in water, and freeze-drying it to obtain cellulose nanofibers;
[0016] (3) subjecting the alkaline solution to acid precipitation and dialysis treatment, taking the supernatant, and freeze-drying it to obtain lignin nanoparticles.
[0017] The homogenization process includes the following steps:
[0018] The cellulose nanofibers are mixed with the lignin nanoparticles, dispersed in a buffer solution, and homogenized in a high-pressure microfluidizer for 5 to 7 times to obtain the lignocellulose;
[0019] The buffer is a phosphate buffer;
[0020] The homogenization pressure is 10000-15000 psi.
[0021] The lignocellulose is acetyl-modified.
[0022] The mass of the wood cellulose is 3-5 wt % of the mass of the polylactic acid particles.
[0023] The polylactic acid particles are pretreated I;
[0024] The pretreatment I is drying at 70-80°C for 3-5h;
[0025] The lignocellulose is subjected to pretreatment II;
[0026] The pretreatment II is freeze drying for 12 to 16 hours and grinding.
[0027] The mixing temperature is 170-175°C.
[0028] The foaming temperature is 150-160°C;
[0029] The foaming time is 2 to 3 hours;
[0030] The foaming pressure is 1-15 MPa.
[0031] The foaming process includes a foaming agent;
[0032] The foaming agent is supercritical carbon dioxide;
[0033] The foaming is carried out in an autoclave.
[0034] Compared with the prior art, the embodiments of the present application have at least the following advantages or beneficial effects:
[0035] This application uses agricultural waste (agricultural straw) as raw material to extract lignocellulose resources, in which lignin is hydrophobic and cellulose is hydrophilic, and then acetylation is improved to promote the dispersion of lignocellulose in polylactic acid to form a stable mixed masterbatch; the mixed masterbatch is extruded and foamed to prepare a bio-based porous foam material. This application makes full use of agricultural waste resources, thereby solving the problem of agricultural waste treatment and reducing the production cost of porous foam materials. DETAILED DESCRIPTION
[0036] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0037] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail below with reference to specific embodiments.
[0038] The features and performance of the present application are further described in detail below in conjunction with the embodiments.
[0039] Example 1
[0040] S1. The corn stalks are mechanically crushed and passed through 600 mesh. The crushed stalk material is boiled in water for 2 hours, removed and drained and dried at 80°C for 3 hours, then soaked in a sodium hydroxide aqueous solution with a concentration of 1 mol / L for ball milling. After ball milling, solids and alkali liquor are filtered to obtain solids, and the solids are washed with deionized water until neutral. The washed solids are dispersed in deionized water and freeze-dried to obtain cellulose nanofibers; the alkali liquor after ball milling and the washing water in the washing step are combined, and hydrochloric acid is used for acid precipitation treatment, and then deionized water is used for dialysis treatment, and the dialyzed supernatant is freeze-dried to obtain lignin nanoparticles; the cellulose nanofibers and lignin nanoparticles are combined to obtain lignocellulose. Then the extracted lignocellulose is acetylated. The specific acetylation process is to disperse the lignocellulose in a mixed solvent of water and ethanol, then add acetic anhydride to react at 80°C for 5 hours, and after the reaction, solid-liquid separation is performed and then washed with clean water and dried.
[0041] S2, dispersing the modified lignocellulose in phosphate buffer to obtain a suspension, placing the suspension in a high-pressure microfluidizer, adjusting the homogenization pressure to 12000 psi, and homogenizing 7 times to obtain modified nano-lignocellulose;
[0042] S3, drying the polylactic acid particles at 75°C for 3 hours, freezing the modified nano-lignocellulose in a liquid nitrogen environment for 12 hours, and grinding it into powder. Adding it into an internal mixer at a mass ratio of 100:5, mixing it at 175°C to obtain a mixed masterbatch;
[0043] S4. The mixed masterbatch is placed in a twin-screw extruder to obtain mixed particles after extrusion. Supercritical carbon dioxide is used as a physical foaming agent. The extruded mixed particles are placed in an autoclave filled with carbon dioxide, maintained at 150°C and 15MPa for 3 hours, and then the pressure is released within 10 seconds to obtain a biodegradable PLA porous foam material.
[0044] Example 2
[0045] S1. The corn stalks are mechanically crushed and passed through 500 meshes. The crushed stalks are boiled in water for 2 hours, taken out and drained, and dried at 80°C for 3 hours, and then immersed in a sodium hydroxide aqueous solution with a concentration of 1 mol / L for ball milling. After ball milling, solids and alkali liquor are obtained by filtration. The solids are washed with deionized water until neutral. The washed solids are dispersed in deionized water and freeze-dried to obtain cellulose nanofibers; the alkali liquor after ball milling and the washing water in the washing step are combined, and acid precipitation treatment is performed with hydrochloric acid, and then dialyzed with deionized water. The dialyzed supernatant is freeze-dried to obtain lignin nanoparticles; the cellulose nanofibers and lignin nanoparticles are combined to obtain lignocellulose. The extracted lignocellulose is then acetylated.
[0046] S2, dispersing the modified lignocellulose in phosphate buffer to obtain a suspension, placing the suspension in a high-pressure microfluidizer, adjusting the homogenization pressure to 15000 psi, and homogenizing for 7 times to obtain modified nano-lignocellulose;
[0047] S3, drying the polylactic acid particles at 75°C for 2 hours, freezing the modified nano-lignocellulose in a liquid nitrogen environment for 12 hours, and grinding it into powder. Adding it into an internal mixer at a mass ratio of 100:3, mixing it at 170°C to obtain a mixed masterbatch;
[0048] S4. The mixed masterbatch is placed in a twin-screw extruder to obtain mixed particles after extrusion. Supercritical carbon dioxide is used as a physical foaming agent. The extruded mixed particles are placed in an autoclave filled with carbon dioxide, maintained at 160°C and 15MPa for 2.5 hours, and then the pressure is released within 10 seconds to obtain a biodegradable PLA porous foam material.
[0049] Example 3
[0050] S1. The corn stalks are mechanically crushed and passed through 500 meshes. The crushed stalks are boiled in water for 3 hours, taken out and drained, and dried at 90°C for 3 hours, and then immersed in a sodium hydroxide aqueous solution with a concentration of 0.8 mol / L for ball milling. After ball milling, solids and alkali liquor are obtained by filtration. The solids are washed with deionized water until neutral. The washed solids are dispersed in deionized water and freeze-dried to obtain cellulose nanofibers; the alkali liquor after ball milling and the washing water in the washing step are combined, and acid precipitation treatment is performed with hydrochloric acid, and then dialyzed with deionized water. The dialyzed supernatant is freeze-dried to obtain lignin nanoparticles; the cellulose nanofibers and lignin nanoparticles are combined to obtain lignocellulose. The extracted lignocellulose is then acetylated.
[0051] S2, dispersing the modified lignocellulose in phosphate buffer to obtain a suspension, placing the suspension in a high-pressure microfluidizer, adjusting the homogenization pressure to 10,000 psi, and homogenizing for 7 times to obtain modified nano-lignocellulose;
[0052] S3, drying the polylactic acid particles at 70°C for 2 hours, freezing the modified nano-lignocellulose in a liquid nitrogen environment for 12 hours, and grinding it into powder. Adding it into an internal mixer at a mass ratio of 100:3, mixing it at 170°C, and obtaining a mixed masterbatch;
[0053] S4. The mixed masterbatch is placed in a twin-screw extruder to obtain mixed particles after extrusion. Supercritical carbon dioxide is used as a physical foaming agent. The extruded mixed particles are placed in an autoclave filled with carbon dioxide, maintained at 160°C and 15MPa for 2.5 hours, and then the pressure is released within 10 seconds to obtain a biodegradable PLA porous foam material.
[0054] Example 4
[0055] S1. The corn stalks are mechanically crushed and passed through 600 meshes. The crushed stalks are boiled in water for 3 hours, taken out and drained, and dried at 95°C for 3 hours, and then immersed in a sodium hydroxide aqueous solution with a concentration of 0.8 mol / L for ball milling. After ball milling, solids and alkali liquor are obtained by filtration. The solids are washed with deionized water until neutral. The washed solids are dispersed in deionized water and freeze-dried to obtain cellulose nanofibers; the alkali liquor after ball milling and the washing water in the washing step are combined, and acid precipitation treatment is performed with hydrochloric acid, and then dialyzed with deionized water. The dialyzed supernatant is freeze-dried to obtain lignin nanoparticles; the cellulose nanofibers and lignin nanoparticles are combined to obtain lignocellulose. The extracted lignocellulose is then acetylated.
[0056] S2, dispersing the modified lignocellulose in phosphate buffer to obtain a suspension, placing the suspension in a high-pressure microfluidizer, adjusting the homogenization pressure to 10,000 psi, and homogenizing for 7 times to obtain modified nano-lignocellulose;
[0057] S3, drying the polylactic acid particles at 75°C for 2 hours, freezing the modified nano-lignocellulose in a liquid nitrogen environment for 15 hours, and grinding it into powder. Adding it into an internal mixer at a mass ratio of 100:3, mixing it at 170°C to obtain a mixed masterbatch;
[0058] S4. The mixed masterbatch is placed in a twin-screw extruder to obtain mixed particles after extrusion. Supercritical carbon dioxide is used as a physical foaming agent. The extruded mixed particles are placed in an autoclave filled with carbon dioxide, maintained at 155°C and 15MPa for 2 hours, and then the pressure is released within 10 seconds to obtain a biodegradable PLA porous foam material.
[0059] Example 5
[0060] S1. The corn stalks are mechanically crushed and passed through 600 meshes. The crushed stalks are boiled in water for 3 hours, taken out and drained, and dried at 95°C for 3 hours, and then immersed in a sodium hydroxide aqueous solution with a concentration of 0.8 mol / L for ball milling. After ball milling, solids and alkali liquor are obtained by filtration. The solids are washed with deionized water until neutral. The washed solids are dispersed in deionized water and freeze-dried to obtain cellulose nanofibers; the alkali liquor after ball milling and the washing water in the washing step are combined, and acid precipitation treatment is performed with hydrochloric acid, and then dialyzed with deionized water. The dialyzed supernatant is freeze-dried to obtain lignin nanoparticles; the cellulose nanofibers and lignin nanoparticles are combined to obtain lignocellulose. The extracted lignocellulose is then acetylated.
[0061] S2, dispersing the modified lignocellulose in phosphate buffer to obtain a suspension, placing the suspension in a high-pressure microfluidizer, adjusting the homogenization pressure to 10,000 psi, and homogenizing for 7 times to obtain modified nano-lignocellulose;
[0062] S3, drying the polylactic acid particles at 75°C for 2 hours, freezing the modified nano-lignocellulose in a liquid nitrogen environment for 15 hours, and grinding it into powder. Adding it into an internal mixer at a mass ratio of 100:3, mixing it at 170°C to obtain a mixed masterbatch;
[0063] S4. The mixed masterbatch is placed in a twin-screw extruder to obtain mixed particles after extrusion. Supercritical carbon dioxide is used as a physical foaming agent. The extruded mixed particles are placed in an autoclave filled with carbon dioxide, maintained at 155°C and 15MPa for 2 hours, and then the pressure is released within 10 seconds to obtain a biodegradable PLA porous foam material.
[0064] In summary, a method for preparing a PLA porous foam material according to an embodiment of the present application has the following advantages: the present application uses agricultural waste (agricultural straw) as raw material to extract lignocellulose resources, wherein lignin is hydrophobic and cellulose is hydrophilic, and then acetylation is used to improve the dispersion of lignocellulose in polylactic acid to form a stable mixed masterbatch; the mixed masterbatch is extruded and foamed to obtain a bio-based porous foam material. The present application makes full use of agricultural waste resources, thereby solving the problem of agricultural waste treatment and reducing the production cost of porous foam materials. The bio-based porous foam material prepared in the present application has stable performance and good thermal insulation effect, and can be used as a thermal insulation material.
[0065] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A method for preparing a PLA porous foam material, characterized in that: The following steps are involved: S1, crushing the biomass material, extracting lignin and cellulose nanofibers therein, and homogenizing them to obtain lignocellulose; S2, mixing the polylactic acid particles and the wood cellulose to obtain a mixed masterbatch, and extruding and foaming to obtain the PLA porous foam material; The biomass material is selected from corn straw, wheat straw, rice husk, rice straw, cotton straw, tobacco straw, sugarcane bagasse, and grape prunings.
2. The preparation method according to claim 1, characterized in that: crushing the biomass material to obtain crushed biomass material; The particle size of the crushed biomass material is 500-600 meshes.
3. The preparation method according to claim 2, characterized in that: The extraction The process includes: (1) boiling and drying the crushed biomass material, soaking it in a sodium hydroxide aqueous solution and performing ball milling to obtain a solid and an alkali solution; (2) washing the solid to neutrality, dispersing it in water, and freeze-drying it to obtain cellulose nanofibers; (3) subjecting the alkaline solution to acid precipitation and dialysis treatment, taking the supernatant, and freeze-drying it to obtain lignin nanoparticles.
4. The preparation method according to claim 3, characterized in that: The homogenization process includes the following steps: The cellulose nanofibers are mixed with the lignin nanoparticles, dispersed in a buffer solution, and homogenized in a high-pressure microfluidizer for 5 to 7 times to obtain the lignocellulose; The buffer is a phosphate buffer; The homogenization pressure is 10000-15000 psi.
5. The preparation method according to claim 1, characterized in that: The lignocellulose is acetyl-modified.
6. The preparation method according to claim 1, characterized in that: The mass of the wood cellulose is 3-5 wt % of the mass of the polylactic acid particles.
7. The preparation method according to claim 1, characterized in that: The polylactic acid particles are pretreated I; The pretreatment I is drying at 70-80°C for 3-5h; The lignocellulose is subjected to pretreatment II; The pretreatment II is freeze drying for 12 to 16 hours and grinding.
8. The preparation method according to claim 1, characterized in that: The mixing temperature is 170-175°C.
9. The preparation method according to claim 1, characterized in that: The foaming temperature is 150-160°C; The foaming time is 2 to 3 hours; The foaming pressure is 1-15 MPa.
10. The preparation method according to claim 1, characterized in that: The foaming process includes a foaming agent; The foaming agent is supercritical carbon dioxide.
Citation Information
Patent Citations
Preparation method of uniform-cell and high-buffer polylactic acid foamed material
CN105462195A
Supercritical fluid injection molding foaming polylactic acid foam material and preparation method thereof
CN111286070A
Lignin-containing biodegradable polyester compound bead foaming material with high crystallization rate and preparation method thereof
CN113736129A
Compatibilizers for polymer-nanocellulose composites
US20180258259A1